Human Adipose Mesenchymal Stromal/Stem Cells Improve Fat Transplantation Performance - Maria Serena Piccinno; Tiziana Petrachi; Marco Pignatti; Alba Murgia; Giulia Grisendi; Olivia Candini; Elisa Resca; Valentina Bergamini; Francesco Ganzerli; Alberto Portone; Ilenia Mastrolia; Chiara Chiavelli; et al. (Cells, 2022)
The resorption rate of autologous fat transfer (AFT) is 40–60% of the implanted tissue, requiring new surgical strategies for tissue reconstruction. We previously demonstrated in a rabbit model that AFT may be empowered by adipose-derived mesenchymal stromal/stem cells (AD-MSCs), which improve graft persistence by exerting proangiogenic/anti-inflammatory effects. However, their fate after implantation requires more investigation. We report a xenograft model of adipose tissue engineering in which NOD/SCID mice underwent AFT with/without human autologous AD-MSCs and were monitored for 180 days (d). The effect of AD-MSCs on AFT grafting was also monitored by evaluating the expression of CD31 and F4/80 markers. Green fluorescent protein-positive AD-MSCs (AD-MSC-GFP) were detected in fibroblastoid cells 7 days after transplantation and in mature adipocytes at 60 days, indicating both persistence and differentiation of the implanted cells. This evidence also correlated with the persistence of a higher graft weight in AFT-AD-MSC compared to AFT alone treated mice. An observation up to 180 d revealed a lower resorption rate and reduced lipidic cyst formation in the AFT-AD-MSC group, suggesting a long-term action of AD-MSCs in support of AFT performance and an anti-inflammatory/proangiogenic activity. Together, these data indicate the protective role of adipose progenitors in autologous AFT tissue resorption.